Israel after Begin - Mahler, Gregory S., 1950- (Albany : State University of New York Press, 1990)
Annotation Fourteen contributions on the nature of Israeli politics in the post- Begin era discuss such topics as: the withdrawal of Israeli forces from Lebanon; the harnessing of the enormous inflation rate; the relationship between Israel and the US; the survival of the Likud Party; tension between religious and secular Israeli Jews; and changes in national electoral strategies of the major parties. Most of the papers (revised for inclusion) were presented at the Israel Studies Association Conference held at the U. of Vermont, June 1987. Paper edition (unseen), $18.95. Annotation copyrighted by Book News, Inc., Portland, OR.
Israel after Begin / Gregory S. Miller -- The legacy of Begin and Beginism for the Israeli political system / Ilan Peleg -- Illegalism in Israeli political culture : theoretical and historical footnotes to the Pollard Affair and the Shin Beth Cover Up / Ehud Sprinzak -- Tehiya as a permanent nationalist phenomenon / Aaron D. Rosenbaum -- Israeli national security in the 1980s : the crisis of overload / Avner Yaniv -- Israeli-Soviet relations under the National Unity Government / Robert O. Freedman -- Israel in the Middle East / Laurie Mylroie -- Israel and Morocco : the political calculus of a 'moderate' Arab state / Mark A. Tessler -- The guarded relationship between Israel and Egypt / Ann M. Lesch -- The not-so-silent partnership : emerging trends in American Jewish-Israeli relationships / George E. Gruen -- The party's just begun : Herut activists in power and after Begin / Alan S. Zuckerman, Hannah Herzogand Michal Shamir -- Better late than never : democratization in the labor party / Myron J. Aronoff -- Beyond the Begin revolution : recent developments in Israel's religious parties / Gary S. Schiff -- Israel's economic policy in the post-Begin era / Yakir Plessner.
Includes bibliographical references (pages 307-344) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Begin, Menachem, -- 1913-1992 -- Congresses; Begin, Menachem, -- 1913-1992; Israel -- Politics and government -- Congresses; Israel -- Foreign relations -- Congresses; Political parties -- Israel -- Congresses; Israël -- Politique et gouvernement -- Congrès.; Israël -- Relations extérieures -- Congrès.; HISTORY; Diplomatic relations; Political parties; Politics and government; Israel; Congress; proceedings (reports); Conference papers and proceedings; Conference papers and proceedings; Actes de congrès.